Quality of Life Assessment in People Living with HIV/AIDS: Clarifying the WHOQOL-HIV and WHOQOL-HIV-Bref Instruments - Pedroso, Bruno; Gutierrez, Gustavo Luis; Duarte, Edison; Pilatti, Luiz Alberto; Picinin, Claudia Tania (IntechOpen, 2011)
None